Current Perspectives on Small Bowel Tumors: Overview of Prevalence, Clinical Manifestations, and Treatment Approaches - Wongsiriamnuey, Thitichai; Limsrivilai, Julajak (Siriraj Medical Journal, 2024)
Small bowel tumors (SBTs) constitute a rare yet increasingly recognized group of gastrointestinal neoplasms, accounting for less than 5% of all gastrointestinal cancers. Despite their infrequency, the incidence of SBTs has exhibited a notable upward trend, underscoring the importance of understanding these diverse and complex tumors. This review consolidates current knowledge on SBTs, encompassing epidemiology, risk factors, clinical manifestations, diagnostic advancements, and treatment modalities. Data from various sources are analyzed to present a comprehensive overview of the evolving landscape of SBTs. Our findings indicate that adenocarcinomas, carcinoid tumors, lymphomas, and gastrointestinal stromal tumors (GISTs) are the common SBTs. While adenocarcinoma and neuroendocrine tumors are the common types of SBTs in the West, GIST and lymphoma are more common in Asia. Common risk factors include genetic syndromes and inflammatory bowel diseases. There is variability in clinical presentations depending on the type of tumors. Although diagnostic challenges persist, advancements in imaging and endoscopic techniques have improved detection rates. Treatment strategies are evolving; surgical resection remains the mainstay for localized disease, augmented by systemic therapies and targeted agents for advanced stages. This review emphasizes the importance of early detection and individualized treatment approaches in improving outcomes for SBT patients. It addresses the need for ongoing research and innovation in managing these tumors.